Crotonylation-related gene GCDH promotes osteoarthritis pathogenesis through flavin adenine dinucleotide signaling: mechanism exploration and experimental validation - Di, Jingkai; Guo, Zijian; Di, Yijing; Zhang, Luyi; Qin, Yingda; Wang, Feida; Xiang, Chuan (Frontiers in Nutrition, 2026)
IntroductionOsteoarthritis (OA) is a prevalent degenerative joint disorder characterized by progressive cartilage degradation and synovial inflammation. This study is designed to elucidate the role of crotonylation genes in OA progression.Materials and methodsThe crotonylation genes exposure and OA outcome data were obtained from the eQTLGen consortium and UK Biobank databases, respectively. Mendelian randomization analysis was employed to establish mechanistic links between crotonylation genes and OA, with subsequent validation conducted through cartilage RNA sequencing (RNA-seq) data. GCDH expression and its regulatory effects on key extracellular matrix (ECM) markers were assessed by Western blot (WB) and quantitative real-time polymerase chain reaction (qRT-PCR) in OA chondrocytes. Moreover, CCK-8, EdU and Transwell assays were utilized to assess differences in chondrocyte proliferation and migration potential at the time of OA versus after GCDH knockdown. Finally, downstream mechanisms were explored using mediation analysis.ResultsThe study identified GCDH as a risk factor contributing to OA susceptibility (OR = 1.048, 95%CI = 1.004–1.093). RNA-seq, qRT-PCR and WB consistently demonstrated significant upregulation of GCDH expression in OA. Furthermore, GCDH was identified as a critical regulator of ECM metabolism in OA pathogenesis. In addition, functional experiments showed that the proliferation and migration ability of chondrocytes was restored in the OA group after GCDH knockdown. Finally, the exploration of the downstream mechanism showed that the flavin adenine dinucleotide mediated the above process.ConclusionThe crotonylation gene GCDH was identified as a potential risk factor for OA pathogenesis, thus providing a novel molecular target and interventions for the development of targeted OA therapeutic strategies.